STUDY OF EFFECTIVE OMNI-DIRECTIONAL VERTICAL AXIS WIND TURBINE FOR LOW SPEED REGIONS - Safarov, Alisher; Mamedov, Rasul (IIUM Engineering Journal, 2021)
This article presents theoretical and experimental studies of an improved vertical axis wind power device that generates electricity in areas with an average wind speed of 3.5-4.5 m/s. An algorithm has been developed for determining the geometrically optimal dimensions of the outer guiding surfaces to improve the efficiency of the device at low wind speeds. The device uses an AFPMG generator with opposite rotation of the stator and rotor. Matlab/Simulink and Solidworks were used to develop a mathematical and physical model of the wind power device. According to the results of the study, it was found that the developed wind power device can reach a rated power of 700 W at a wind speed of 8 m/s. The use of the device in areas with low wind speed is based on the possibility of increasing the efficiency of work by 5-10% at an average wind speed lower than that of other types of wind power devices. ABSTRAK: Artikel ini memaparkan kajian teori dan eksperimen berkenaan alat kuasa angin paksi menegak yang diperbaharui dan menghasilkan tenaga elektrik di kawasan kelajuan angin berpurata 3.5-4.5 m/s. Algoritma telah dibangunkan bagi menentukan dimensi optimum geometri permukaan berpandu luar dalam meningkatkan kecekapan peranti pada kelajuan angin yang kurang. Peranti ini menggunakan penjana AFPMG dengan putaran stator dan rotor yang berlawanan. Matlab/Simulink dan Solidworks digunakan bagi menghasilkan model matematik dan fizikal peranti tenaga angin. Berdasarkan dapatan kajian, didapati bahawa alat tenaga angin yang dibangunkan ini dapat mencapai daya kuasa sebanyak 700 W pada kecepatan angin 8 m/s. Penggunaan alat ini di kawasan kurang kelajuan angin berkemungkinan meningkatkan efisiensi purata kerja sebanyak 5-10% pada kelajuan angin rendah, iaitu lebih rendah daripada segala jenis peranti tenaga angin lain.